Students’ Perceptions about Feedback Practices During Academic Writing Course: A Survey Study - Esty Nurjanah (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2021)
In Indonesian context, there is still very little research regarding how students’ voicing their perception on the use of feedback practices by their teachers. Therefore, to fill this gap, this research is aimed to describe students’ perception through a survey about their experiences in dealing with feedback practices by their teacher. This study involved 75 students from English department students of English courses and college. The Responsive Pedagogy Questionnaire (RPQ) was used in this study. There were 24 items with 4 Likert points in data completion. To analyze the data, Microsoft Excel was used by the researcher. Findings showed that teachers’ feedback practice matters to the students (M=3.70). It means that the participants have positive responses toward teacher feedback practices. These findings have pedagogical implications that teachers of academic writing can consider not only to the instructions but also to the content or the material.